Phytochemical constituents and nutrient evaluation of date palm (Phoenix dactylifera, L.) pollen grains - Al-Samarai, A. H.; Al-Salihi, F.G; Al-Samarai, R.R (Tikrit Journal of Pure Science, 2023)
The pollen of date palm -DPP (Phoenix dactylifera L. variety El- Ghannmi Ahmar.) has been analyzed for the main phytochemical composition , nutrient and mineral composition. The phytochemical screening of chemical constituents of the plant showed that the DPP grains contains phytosterols, flavonoids, alkaloids, protein, carbohydrates, glycosides, phenolic compounds, tannins, terpenoids, saponins, coumarins, lignin, oil and fats, with absent of quinones. The quantitative contents of  alkaloids, tannin, phenolic compounds and sterols were (2416±0.034, 2279.6±35.769, 115±5 and 110.1±0.87)   mg/100g in DPP grains. While the moisture content of palm pollen grains was 8.041 ± 0.1%, and 91.959 ± 0.1 % for the total solids. Values 0.113±0.003 % and 5.585 ± 0.144 % were estimated for crude fiber and ash contents respectively. Crude fat content of DPP grains was 7.678 ±0.149%, 19.45%,  for crude protein and 26.25±0.315 g/100g for carbohydrates ,the energy value was 291.902 Kcal/100g. The predominant  minerals were potassium  73.5 mg/g, followed by magnesium 19.6 mg/g , calcium 10.8 mg/g and iron 8.5 mg/g. Comparable  amounts of  sodium 4.34 mg/g and copper 3.658 mg/g with equal amounts of  molybdenum, nitrogen and boron (3.169, 3.11 and 3.024) mg/g respectively were found in DPP grains. Palm pollen also contain useful amount of zinc 2.799 mg/g, manganese 2.702 mg/g, selenium 2.51 mg/g, cobalt 1.986 mg/g, nickel 1.698 mg/g and cadmium 0.12 mg/g. From all the results we can conclude that the date palm pollen was as rich source of antioxidant, energy, and important minerals, so   its suitability as a regular component in human diet.